2014
DOI: 10.1186/1471-2458-14-668
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of consistent condom use among recently initiated and traditionally circumcised men in the rural areas of the Eastern Cape Province, South Africa

Abstract: BackgroundConsistent use of condoms is the most effective method of preventing STIs including HIV. However, recent evidence suggests that limited knowledge about HIV prevention benefits from male circumcision leads to inconsistent condom use among traditionally circumcised men. The aim of this paper is to report on the prevalence of consistent condom use and identify its psychosocial correlates to inform future HIV prevention strategies among traditionally circumcised men in rural areas of the Eastern Cape Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
5
23
1
Order By: Relevance
“…With an alpha of 0.05 and assuming 80% power, a sample size of 250 was shown to be required to detect an association strength of 2.04 [12] or higher, given the proportion of 41.7% of affected individuals who were not exposed and 52.9% who were exposed.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…With an alpha of 0.05 and assuming 80% power, a sample size of 250 was shown to be required to detect an association strength of 2.04 [12] or higher, given the proportion of 41.7% of affected individuals who were not exposed and 52.9% who were exposed.…”
Section: Sample Sizementioning
confidence: 99%
“…Most studies tend to extend their definition of condom use, for example, a study conducted in South Africa used a score consisting of three items: "always", "sometimes" and "never" [12]. However, given that the World Health Organisation (WHO) has reported that condoms must be used during 100% of sexual activity to effectively prevent STIs, for the purposes of the current study, inconsistent condom use was defined as condom use at a frequency less than 100% during sexual activity [4].…”
Section: Questionnaire and Definition Of Variablesmentioning
confidence: 99%
“…13,16 Using condoms also provides a safe family planning option that has no known side effects, thus providing dual protection against unwanted pregnancies and STIs. Globally, condom programs are recommended as highly effective in preventing HIV transmission, adolescence pregnancy, and are generally regarded as acceptable to young people.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, more specifically, a few studies have used the Theory of Planned Behaviour as a framework to research gender power imbalances in the intention to use condoms [33], the role of individual and group factors in intentions to use condoms [34], adolescent condom use behaviour [25,35,36], the influence intention has on behaviour among university students [37], and condom use motivation in traditional male circumcision initiates [38]. These studies also vary in their prediction of the most influential cognitive constructs, and some also show a clear gender difference in their predictability where both sexes were sampled.…”
Section: Introductionmentioning
confidence: 99%
“…Young men between the ages of 18 and 35 are particularly at a high risk of HIV infection. Given the gender imbalances in HIV transmission, it is expected that developing culturally sensitive interventions targeting young men will help increase safer sexual practices [38]. A focus on young men can also help impact the gender imbalances reported by some studies that, in heterosexual relationships, women do not use condoms mainly because of their sexual partner’s refusal to use them [10,11].…”
Section: Introductionmentioning
confidence: 99%